Assessment of climate change adaptation interventions for livestock through a gender lens - Chan-Dentoni, Jacqueline; Kacha, Gabrielle; Rosenstock, Todd S. (2022)
A rapid evidence review of scholarly and grey literature was conducted to assess the gender impacts of climate-smart livestock interventions. Five gender impact indicators were established to identify the effects on women’s time, labor/drudgery, access to knowledge/financial resources, and food/nutritional security. 117 articles were quantitatively assessed using adapted methods from grounded theory and outcome harvesting to collect data on shifting to small ruminants, improved forage, shade for livestock, and credit. Recurring findings showed that there is women’s engagement varies based largely on access to land, training, extension services, and financial services. Women were also shown to predominantly take on additional responsibilities and tasks related to introduced technologies, while often not reaping the benefits directly. Understanding and addressing these inhibiting and enabling factors can work towards increasing women’s empowerment and improve the sustainability and success of the livestock interventions